Beyond Doctrines of Dominance: Conceptualizing a Path to Legal Recognition and Affirmation of the Manitoba Métis Treaty - Vermette, D'Arcy G. (Université d'Ottawa / University of Ottawa, 2012)
In 1869-70 the Métis of the Red River region in Manitoba resisted the transfer of their homeland from the Hudson’s Bay Company to Canada. The Métis people responded to this transfer by blocking Canadian surveyors, government officials, and taking control of the territory through the establishment of representative institutions. Eventually, the Métis negotiated favourable terms with Ottawa which, this thesis argues, represented according to law, and to the Métis, a treaty. This thesis argues that this treaty was intended to protect the Métis homeland and provide political and social protections. The Manitoba Métis Treaty was intended to guarantee the Métis a land base in Manitoba the total size of which was to be 1.4 million acres. The reservation of this land came with protective obligations so that the entire community would receive a benefit from such lands. While Canada has developed a body of treaty law which will be used to interpret the Manitoba Métis Treaty, matters were convoluted by the enshrinement of this treaty agreement in the Manitoba Act of 1870, a document which would gain constitutional status a year later. The impact of this legislative history has led some researchers to link government obligations entirely to the Act, rather than to the negotiated agreement. Indeed, it would seem that the negotiations have been, for the most part, understood as nothing more than conversations. I reject that position and argue that both the negotiations and the Act must be taken into consideration when assessing the obligations undertaken by the Crown. The unique history of the Manitoba agreement means that Canada was under both constitutional and treaty law obligations to uphold the negotiated agreement between itself and the Métis. This thesis argues that not only is the treaty the correct legal interpretation of the events of 1869-70 but that the government of Canada failed to honour its commitments in several meaningful ways. The approach utilized in this thesis is designed to be reliant upon the basic structure and doctrines of Canadian law but to do so in a manner which gives weight to the Métis voice. It is neither a critique which is wholly internal to Canadian law nor is it completely dismissive of Canadian law. Instead, this thesis will illustrate that with only minor adjustments to the application and interpretation of colonial law, the Manitoba Métis Treaty could find a more receptive audience in Canadian legal thought. In the face of a reasonable alternative, such a project can allow other researchers to question why the courts have chosen a path which denies reception of Métis voice, community and culture in Canadian law.